"Ballerinas on the Dole:" Dance and the U.S. Comprehensive Employment Training Act (CETA), 1974–1982. Issue 3 (7th December 2017) - Hooper, Colleen
Abstract : The Comprehensive Employment Training Act (CETA) was a program of the US federal government that employed dancers, performers, and other artists to provide public service in municipalities across the country from 1974 to 1982. This article focuses on dancers who participated in the CETA program. It describes this important source of government funding for dance and the arts that has been largely overlooked in scholarship. Through an analysis of one New York City CETA dance community performance site, it reveals the tensions present in the construct of "dance as public service." This case study is offered as an exemplar of how the largest CETA arts program in the United States served a wide range of artists and communities. Through an analysis of two CETA dance performances at the Arthur Kill Correctional Facility in New York City, the article questions who was served by dance as public service.